Imbue problem solving skills in law school curriculum to off-set adversarial ‘hired-gun’ mind-set - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (LexisNexis, 2019)
Alternative modes of dispute resolution such as mediation and conciliation are, in most circumstances able to improve the strain relationship between the disputants. Only when the parties are unable to resolve the dispute amicably would adjudication before the court become necessary as the last resort. To this end, members of the legal fraternity would have to place their clients’ interests above their own, and to discard their litigation based mindset, promoting mediation although it may lead to less revenue. Individual lawyers who earn a living from the fee he/she charges the client may not be receptive of mediation because there would be a lesser role for them if it was implemented. Hence, this adversarial ‘hired-gun’ mindset should be steered away from. This paper aims to propose a change in the law school curriculum which would shift away from the adversarial nature of teaching and training of lawyers and to place an emphasis on dispute settlement as opposed to litigation. Would-be lawyers ought to be taught the basic concept of alternative dispute resolution at the earliest stage of their legal education. At the same time, mediation skills should be integrated into substantive law subjects and to be reflected in the curriculum via teaching and examinations. By having such a programme, it is submitted that the would-be lawyers should be inclined towards solving client’s problem through alternative modes instead of litigating disputes.